2013
DOI: 10.1111/aji.12137
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Clinical Cellular Immune Markers in Women with Recurrent Pregnancy Loss

Abstract: Differences in NK cell percentages, NKC and Th1/Th2 cell ratio differentiated RPL from fertile controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
96
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 56 publications
6
96
2
6
Order By: Relevance
“…Cluster #413 is probably an aggregate of monocytes and CD8 T cells. Previous studies have shown alterations in NK cell populations during pregnancy, particularly in association with different pregnancy outcomes 29, 30. The effects of pregnancy on circulating T cell populations are less known, although we and others have shown a subtle alteration of T cell cytokine patterns during pregnancy (31, 32, 33, and our data not shown).…”
Section: Resultssupporting
confidence: 38%
“…Cluster #413 is probably an aggregate of monocytes and CD8 T cells. Previous studies have shown alterations in NK cell populations during pregnancy, particularly in association with different pregnancy outcomes 29, 30. The effects of pregnancy on circulating T cell populations are less known, although we and others have shown a subtle alteration of T cell cytokine patterns during pregnancy (31, 32, 33, and our data not shown).…”
Section: Resultssupporting
confidence: 38%
“…Women with miscarriages and preeclampsia as well, have NK1 and NKT1 shift that produce high amounts of IFN-γ and little IL-4 in peripheral blood [11]. Therefore, cellular immune-regulation including innate immunity is critical for human reproduction.Women with RPL and MIF have significantly higher NK-cell levels and cytotoxicity, and dysregulated cytokine production patterns as compared to normal controls [10,12]. Activating receptor expression on NK cells was significantly increased, while inhibitory receptor expression was significantly decreased in vivo [13].…”
mentioning
confidence: 95%
“…Women with RPL and MIF have significantly higher NK-cell levels and cytotoxicity, and dysregulated cytokine production patterns as compared to normal controls [10,12]. Activating receptor expression on NK cells was significantly increased, while inhibitory receptor expression was significantly decreased in vivo [13].…”
mentioning
confidence: 95%
See 2 more Smart Citations